Addressing Health-Care System Inequities in the Management of Erectile Dysfunction: A Call to Action. Issue 5 (October 2020) - Burnett, Arthur L.; Edwards, Natalie C.; Barrett, Tonya M.; Nitschelm, Krista D.; Bhattacharyya, Samir K.
Erectile dysfunction (ED) is a common, burdensome, and costly urologic condition strongly related to all aspects of general health, from physical to mental. ED has profound consequences as it may interfere physical well-being, quality of life (QoL), self-esteem, relationships, self-worth, and productivity. It is therefore important to ensure that all types of effective ED treatments are consistently accessible to patients. While federal and state mandates ensure access to treatment for women's breast health, female-factor infertility, and gender affirmation to ensure that these individuals do not experience a diminished QoL, there are no comparable mandates for men's sexual and reproductive health. The burden of ED necessitates a call to action to improve the accessibility of ED treatments. The call to action steps include: (a) coverage for pharmacological, surgical, and other ED treatments should be viewed in the same way as coverage for other health issues, whether male or female and regardless of the stages of treatment, physical dysfunction, or physical changes; (b) American Urological Association (AUA) guidelines for the management of ED should be followed, including implementation of templates in electronic medical records (EMRs) to support adherence to the guidelines; and (c) coverage criteria should explicitly state that the criteria are intended to support gender equity for sexual and reproductive health care and should not be used to prevent men from receiving medically necessary ED treatments. This call to action offers a pathway to support every man who seeks treatment for ED as a medically necessary intervention by removing systemic health-care barriers.